Venture capitalists’ investment selection criteria in CEE countries and Russia - Zinecker, Marek; Bolf, David (Business: Theory and Practice, 2015)
This article deals with findings of a survey in the Central and Eastern European (CEE) and Russian venture capital markets. The main aim of this study is to explore the following issues: Which criteria play an essential role in the selection of business proposals by firms investing venture capital in the CEE and Russian markets? What are the key characteristics of an investment selection process? And, in addition: Who are the investors in these markets? The nature of this study is explorative. It relies on primary data that were collected using a semi-structured questionnaire. The data were processed by statistical methods reflecting their nature and quantity. Descriptive methods served as basic statistical analyses. The survey results, which provide a number of unique insights into the field, are subsequently compared with findings which were published in similar studies undertaken in well-developed capital markets. This study supports the thesis that, when considering business proposals, above-average attention has been paid to criteria concerning the competitive advantage of the product and its potential to generate high returns. Our survey also confirms conclusions drawn from other studies which identify the size of the market and its growth rate as the most significant criteria characterizing the market. The crucial criterion in the category dedicated to management’s experience in the initial stage of the business life cycle is the management’s familiarity with the target market although investors emphasize its lower significance compared to the product and market characteristics. By publishing empirical data, an important signal regarding up-to-date evaluative criteria and their weight is sent both to prospective venture capitalists and investee companies operating under specific conditions of the CEE countries and Russia.